Visible light mediated, metal and oxidant free highly efficient cross dehydrogenative coupling (CDC) reaction between quinoxalin-2(1H)-ones and ethers - Mane, Kishor D.; Kamble, Rohit B.; Suryavanshi, Gurunath (New Journal of Chemistry, 2019)
The efficient and metal free, white light mediated 3C alkylation of quinoxalin-2(1H)-ones via a cross dehydrogenative coupling reaction with cyclic ethers using eosin Y as a photocatalyst is described. This reaction has broad substrate scope and strong functional group tolerance with good to excellent yields.

Visible-light-induced controlled oxidation of N-substituted 1,2,3,4-tetrahydroisoquinolines for the synthesis of 3,4-dihydroisoquinolin-1(2h)-ones and isoquinolin-1(2H)-ones - Bansode, Ajay H.; Suryavanshi, Gurunath (Advanced Synthesis & Catalysis, 2021)
A visible light-rose bengal-TBHP mediated, controlled oxidation of N-substituted 1,2,3,4-tetrahydroisoquinolines is developed for the synthesis of 3,4-dihydroisoquinolin-1(2H)-ones and isoquinolin-1(2H)-ones. The present method feature's a broad substrate scope, good functional group tolerances, and the products were prepared in good to excellent yields. The developed methodology further demonstrated in the synthesis of isoindolo[2,1-b] isoquinolin-5(7H)-one (topoisomerase-I inhibitor).
Keywords: 2; 3; 4-Dihydroisoquinolin-1(2H)-one; 4-tetrahydroisoquinolines; Isoquinolin-1(2H)-one; N-substituted 1; Oxidation; Photocatalysis

Visible light-promoted, photocatalyst-free C(sp(2))-H bond functionalization of indolizines via EDA complexes - Mane, Kishor D.; Rupanawar, Bapurao D.; Suryavanshi, Gurunath (European Journal of Organic Chemistry, 2022)
The catalyst and additive-free, photo-driven cross dehydrogenative coupling (CDC) reaction initiated by electron donor-acceptor (EDA) complexes between electron rich indolizines and electron poor quinones has been demonstrated. This green transformation reveals the advantages of operational simplicity, mild reaction conditions and good functional group tolerances.
Keywords: Blue LED; CDC; EDA; Indolizine; Quinone